Carbonaceous material export from Siberian permafrost tracked across the Arctic Shelf using Raman spectroscopy; Cryosphere; Vol. 12, iss. 10 - Sparkes R. B. Robert; Maher M. Melissa; Blewett J. Jerome; Selver A. D. Ayca Dogrul; Gustafsson O. Orjan; Semiletov I. P. Igor Petrovich; Van D. B. Dongen Bart (2018, 2018)
Title screen